2013
DOI: 10.1159/000353624
|View full text |Cite
|
Sign up to set email alerts
|

Positive Cytology Findings and a Negative Histological Diagnosis of Papillary Thyroid Carcinoma in the Thyroid: Is It a False-Positive Cytology or a Disappearing Tumor

Abstract: Background: It infrequently occurs that cytologic diagnosis of papillary thyroid carcinoma (PTC) cannot be confirmed by histology after surgery. This phenomenon may be a false-positive cytology or a true disappearing tumor. Objectives: We evaluated patients who had consistent findings of PTC at fine needle aspiration cytology (FNAC) and no evidence of PTC in surgical specimens. Methods: Positive cytology findings and a negative histological diagnosis of PTC in the thyroid was defined as thyroid nodules with FN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 16 publications
1
15
0
Order By: Relevance
“…The pathological diagnosis and classification of PTC are usually based on the microscopic appearance of biopsy specimens . Fine‐needle aspiration cytology (FNAC) is widely accepted as a rapid, cost‐effective, and safe method for the diagnosis of thyroid nodules . The positive predictive value of FNAC for malignancy according to the Bethesda system is 97%‐99%, and the sensitivity and specificity of thyroid FNAC have been reported as 65%‐99% and 72%‐100%, respectively …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The pathological diagnosis and classification of PTC are usually based on the microscopic appearance of biopsy specimens . Fine‐needle aspiration cytology (FNAC) is widely accepted as a rapid, cost‐effective, and safe method for the diagnosis of thyroid nodules . The positive predictive value of FNAC for malignancy according to the Bethesda system is 97%‐99%, and the sensitivity and specificity of thyroid FNAC have been reported as 65%‐99% and 72%‐100%, respectively …”
Section: Introductionmentioning
confidence: 99%
“…In this situation, a nodule is underestimated and may be later diagnosed as a malignancy. The rate of false‐positive FNAC for thyroid nodules has been reported as 2%‐10% . The mean risk of malignancy for lesions classified as suspicious for malignancy (class V) and malignant (class VI) is 75.2% and 98.6%, respectively .…”
Section: Introductionmentioning
confidence: 99%
“…Another study at Asan Medical Center reported six cases of disappearing PTC. All of these cases had malignant FNA diagnosis, however, none of the specimens showed malignant cells on resection (18). Another interesting finding reported by this group showed that two of the six cases had lymph nodes positive for PTC with no malignancy in thyroid gland.…”
Section: Discussionmentioning
confidence: 66%
“…In the literature, vanishing tumors of the prostate have been reported for the past few years, the incidence of which is on a decline (15,16). The vanishing tumor phenomenon has been recently described in thyroid gland by some authors (17,18).…”
Section: Original Articlementioning
confidence: 99%
“…Jang et al analyzed cases which appeared malignant in cytology examination and proved benign on HP verification [29]. In the literature there are many descriptions of changes that may emerge in the thyroid gland as a result of multiple punctures, such as hemorrhage, vascular thrombosis, fibrosis, infarction, fibrinoid necrosis, cystic degeneration, vascular and capsular pseudoinvasion, angioinvasion and cellular atypia [30,31,32].…”
Section: Discussionmentioning
confidence: 99%